CT angiography and Doppler ultrasound evaluation of congenital portosystemic shunts - Öznur Boyunağa; Melih Akyüz; Mehmet Öztürk; Enes Gürün; Ahmet Sığırcı; İsmail Akdulum (Acta Medica Alanya)
Aim: The aim of the study was to describe the Doppler ultrasonography and computed tomography findings that should be considered in the diagnosis and treatment of congenital portosystemic shunts.Methods: Archive retrospectively scanned. In consideration of shunts: communication type and aneurysm were defined. Additional imaging modalities were utilized.Results: 11 patients were included in the study. The ages ranged from 0 to 158 months. There were two patients with shunt connecting segment-4 portal vein - middle hepatic vein, two patients with segment-3 portal vein - left hepatic vein, two patients with left portal vein – middle hepatic vein, two patients with portal vein - left renal vein, two patients with portal vein -inferior vena cava, and one patient with portal vein - perirectal venous plexus.Conclusion: Some classifications used in congenital portosystemic shunts are insufficient in guiding treatment. Elaborate definition of the imaging findings including the involved vessels, type of communication, and presence of aneurysm or dilated vessels is of the prime importance for tailoring clinical management of the patients.